Between Structural Theory and Construction Practice: The Role of Drawing in Pier Luigi Nervi’s Ribbed Floor Slabs (diségno, 2026)
Among the many structural solutions that characterize the work of Pier Luigi Nervi (1891-1979), the leading Italian figure in twentieth-century structural engineering, the ribbed floor slabs arranged according to the isostatic lines of bending represent an emblematic outcome of his synthesis of structural logic, constructive efficiency, and expressive quality. In this solution more than in others, drawing plays a decisive role in translating the static principle into built architecture, acting as a critical instrument of selection: through drawing, among the multiple configurations referable to a single guiding principle, those capable of combining constructive correctness with expressive effectiveness are identified. [read more]